POTENSI HAND SANITIZER EKSTRAK ETANOL BUNGA GLETANG (TRIDAX PROCUMBENS.L) SEBAGAI ANTIBAKTERI TERHADAP STAPHYLOCOCCUS AUREUS - Qonitah, Fadilah; Valerie Novia Ramadhani, Feby; Ahwan (FARMESTRA: Jurnal Pelayanan dan Teknologi Kefarmasian Indonesia, 2025)
The gletang flower is a plant with potential for development as a hand sanitizer. The gletang flower contains compounds such as flavonoids, alkaloids, saponins, tannins, and phenols, which have been shown to inhibit the growth of Staphylococcus aureus bacteria. This study aims to determine the statistical data and antibacterial effects of hand sanitizers made from gletan flower ethanol extract on the growth of Staphylococcus aureus bacteria. The hand sanitizer was prepared with gletan flower ethanol extract in four formulas: Formula 0, Formula 1, Formula 2, and Formula 3. Testing of the physical properties of the hand sanitizer included organoleptic testing, homogeneity, pH, viscosity, and spreadability. The antibacterial activity was tested using the disc test method, and the data was analyzed using the Kruskal-Wallis test. The results of the study show that all formulations exhibit good physical properties and antibacterial activity. The antibacterial activity of the positive control was measured with an average inhibition zone of 9.8 ± 0.52 mm. Formula 1 yielded an average inhibition zone of 9.2 ± 0.05 mm, followed by Formula 2 with 12.06 ± 0.07 mm and Formula 3 with 14.25 ± 0.31 mm. The negative control showed no inhibition zone of 0 ± 0.00 mm. The conclusion of this study is that all three formulas of the hand sanitizer made from gletang flower ethanol extract exhibit good physical properties and have been shown to have antibacterial activity against Staphylococcus aureus, with significant differences.